2002
DOI: 10.1046/j.1365-2869.2002.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of fatal occupational accidents – relationship to sleeping difficulties and occupational factors

Abstract: Very little is known about the association between sleep and (fatal) occupational accidents. This study investigated this relationship using register data of self‐rated sleep difficulties, together with occupational and demographic characteristics. The variables were related to subsequent occupational fatal accidents. A national sample of 47 860 individuals was selected at regular intervals over a period of 20 years, and interviewed over the phone on issues related to work and health. The responses were linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
138
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(149 citation statements)
references
References 11 publications
5
138
1
2
Order By: Relevance
“…Poor sleep is prospectively associated with an increased risk of myocardial infarction, particularly when combined with increasing resting heart rate 1) . Poor sleep is also prospectively related to fatal accidents at work and accident risk is considerably increased in relation to irregular work hours 2) . Good sleep quality has been associated with better physical health 3,4) and greater psychological well-being 5,6) .…”
mentioning
confidence: 99%
“…Poor sleep is prospectively associated with an increased risk of myocardial infarction, particularly when combined with increasing resting heart rate 1) . Poor sleep is also prospectively related to fatal accidents at work and accident risk is considerably increased in relation to irregular work hours 2) . Good sleep quality has been associated with better physical health 3,4) and greater psychological well-being 5,6) .…”
mentioning
confidence: 99%
“…Åkerstedt et al (36) reported an association between disturbed sleep and fatal occupational accidents in a large-scale study. The relative risk was much higher among men compared with women (OR Sleep disturbances and occupational accidents 2.3, 95% CI 1.56-3.38), but no separate analysis of the absolute risk for women was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The few prospective studies within this field are limited by not being population based (35) or only including fatal accidents (36). Furthermore, to our knowledge, no studies have previously focused on sleep disturbances and work injuries solely among women.…”
mentioning
confidence: 99%
“…It is considered to be associated with fatigue, sleepiness, decreased alertness, concentration and mood disturbances, and so forth [10][11][12][13][14][15], although there still remains discrepancy about how to assess daytime impairments objectively [16][17][18][19]. In the long run, daytime deficits heighten the risk of absenteeism, impaired work performance [2,[20][21][22], and higher odds for automobile accidents [23,24]. The disturbances have resulted in high economic burden [25,26].…”
Section: Introductionmentioning
confidence: 99%